Mathematical Learning Based on Multymedia at MTs Sabilul Muhtadin, Bangka District - Euis Asriani -; Ririn Amelia (Pengelola Jurnal Politeknik Negeri Ketapang, 2021)
The aim of this community service project was to develop students motivation of MTs Sabilul Muhtadin in mathematical learning based on multimedia. This approach used to créate mathematical learning in fun, interested, and easy ways to be understood, The participants were 30 (thirty) students of VIII grade. For concluding the effectivity of the approach, disributed a questionary in the end of learning meeting. The collected data was analyzed by descriptive statistic in pie diagram. At satisfaction item, the highest percentage was at group that feel satisfied at 70%. At interested item, 66.67% students were interested to learn mathematics with multimedia approach. At motivation, encouragement, and activeness, the highest proportion was at motivated, to be encouraged, and active group, namely at 60% percentage, respectively. Toward this project, can be concluded that mathematical learning based on multimedia approach, generally improve the satisfaction, interested, encouragement, activeness, and motivation. Toward this project, can be concluded that mathematical learning based on multimedia approach, generally improve the satisfaction, interested, encouragement, activeness, and motivation.